Artificial intelligence and machine learning in business management concepts, challenges, and case studies - Panda, Sandeep Kumar 1985- (CRC Press, 2022)
"The focus of this book is to introduce Artificial Intelligence (AI) and Machine Learning (ML) technologies into the context of Business Management. With the maturing use of AI or ML in the field of business intelligence, this book examines several projects with innovative uses of AI beyond data organization and access. It follows the Predictive Modeling Toolkit for providing new insight on how to use improved AI tools in the field of business. Taking a multidisciplinary approach for using AI, this book provides a single comprehensive reference resource for undergraduate, graduate, business professionals, and related disciplines"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on October 04, 2021)
Keywords: Management -- Technological innovations; Artificial intelligence -- Industrial applications; Gestion; Innovations; Intelligence artificielle; Applications industrielles; BUSINESS & ECONOMICS / Management; Artificial intelligence; Industrial applications; Management; Technological innovations